PEMANFAATAN BIOCHAR SEKAM DAN KOMPOS JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa) PADA TANAH ORDO ULTISOL - WELLY HERMAN; ELARA RESIGIA (Universitas Lancang Kuning, 2018)
ABSTRACT The aim of this study were (1) to determine the effect of rice husk biochar and rice straw compost on growth and production rice (Oryza sativa) and (2) to determine the ability of rice husk biochar and rice straw compost in providing nutrients to Ultisol. The research was carried out February – July 2018 in Sungai Abang Village, Lubuk Alung Regency, Padang Pariaman. Research applied Random Group Design with 5 treatment : 0% Rice husk biochar + 0% Rice straw compost, 100% Rice husk biochar + 0% Rice straw compost, 75% Rice husk biochar + 25% Rice straw compost, 50% Biochar rice husk + 50% Rice straw compost and 25% Rice husk biochar + 75% Rice straw compost. Observations were made on soil and crops including initial soil analyzes ie before treatment was given, soil analysis after incubation, and final soil analysis (pH, N-total, P-available, K-dd, Ca-dd, Mg-dd and Sulfur) and plant observations include plant height, the productive of tiller, total of tiller and weight of grain per hectare. From the research that has been done can be concluded (1) the use of rice husk biochar and rice straw compost affect the growth and production of rice plants seen in the treatment of 75% rice husk biochar + 25% Rice Straw rice husk biochar with the number of productive tillers of 29 tillers and production of rice plants as much as 8,238 tons / ha and (2) the use of rice husk biochar and rice straw compost is able to provide nutrients in Ultisol indicated by increasing pH, N, P, K, Ca, Mg and S.